Gait analysis in ankylosing spondylitis. Issue 7 (July 1992) - Zebouni, L; Helliwell, P S; Howe, A; Wright, V
Abstract : A study was conducted to compare the gait pattern of 12 patients with ankylosing spondylitis with axial disease only with that of 11 healthy controls using a telemeterised electrogoniometer gait analysis system. The reproducibility of the gait variables was found to be acceptable. Angles for movement at the hip and knee were less in patients with ankylosing spondylitis, but hip/knee angle ratios did not differ between the two groups. The stride length was shorter in the patients with ankylosing spondylitis. These findings are due to the increased rigidity of the spine, which results in decreased shock absorption and consequently a more cautious gait pattern in the absence of clinically and radiologically detectable peripheral joint disease.